1999
DOI: 10.1177/0739986399211003
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assessment of Linguistic Skills by Bilingual Hispanics

Abstract: This study examines the ability of bilinguals to judge their linguistic competence. Participants evaluated their Spanish and English language skills both before and after administration of the Woodcock-Muñoz Language Survey, which provided an objective measure of these skills. Self-assessments were more accurate for Spanish than for English and, in the case of English, varied with the skill being rated. Feedback from the objective test improved self-rating accuracy more for Spanish than for English. There was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
59
0
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 33 publications
3
59
0
4
Order By: Relevance
“…In a large Hispanic sample, correlations between self-rated and objectively assessed proficiency were .46 for L2 and .61 for LI. Similar results have been reported by Delgado et al (1999). Although other types of biases and response sets might still have operated to compromise the validity of the LI self-ratings in the present study, the results of multitrait-multimethod (MTMM) analyses reported by Guglielmi (2008), as well as the evidence presented earlier in this article about the reliability and validity of the LI proficiency measure provide some reassurance about the usefulness of those ratings.…”
Section: Limitations Of the Studysupporting
confidence: 89%
“…In a large Hispanic sample, correlations between self-rated and objectively assessed proficiency were .46 for L2 and .61 for LI. Similar results have been reported by Delgado et al (1999). Although other types of biases and response sets might still have operated to compromise the validity of the LI self-ratings in the present study, the results of multitrait-multimethod (MTMM) analyses reported by Guglielmi (2008), as well as the evidence presented earlier in this article about the reliability and validity of the LI proficiency measure provide some reassurance about the usefulness of those ratings.…”
Section: Limitations Of the Studysupporting
confidence: 89%
“…62 There are, to be sure, typical differences between native and non-native competence, verified in research that heeds other distinctions. For instance, Delgado et al 1999 find their subjects to be better at the oral mode in their native language, while they may be better at the written mode in a second language. Cf., however, § 3.3.1.1.1.…”
Section: The Language Competence Quotientmentioning
confidence: 99%
“…This is the exact opposite of what Taylor (1988:153) claims for Chomskyan competence.-It is an interesting issue to what extent a person is aware of the relativity of his language competence and can even assess his own competence in a particular language correctly. The issue is addressed in Delgado et al 1999. The first question is answered with a clear 'yes' for both native and second languages, while the second question receives a mixed and problematic answer in that study.…”
mentioning
confidence: 99%
“…They further argue, as many others (e.g. Delgado et al 1999;Dö rnyei 2007;Lemmon and Goggin 1989;McKinney and Priestly 2004), that, methodologically, the heavy reliance on questionnaires leads to a number of problems, including the distillation of complex issues and experiences into a limited number of assessable constructs; the assumption that all informants will equally understand and engage with the concepts/constructs assessed via a questionnaire (e.g. equally 'understanding' references to 'culture', 'identity'); and the 'over-reliance' on subjective evaluations, which may not reflect actual performance or account for the variables which influence language use in reality (e.g.…”
Section: 'Identity' As a Key Variablementioning
confidence: 93%